Determinants of Total Compensation for Auto Bodily Injury Liability Under No-Fault: Investigation, Negotiation and the Suspicion of Fraud - Derrig, Richard A.; Weisberg, Herbert I. (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2004)
Auto Bodily Injury Liability claim payments are predominantly negotiated settlements, with less than two percent the result of complete litigation and jury trials. All settlements consist of a combination of claimed economic loss, called special damages, and a payment for “pain and suffering”, called general damages. The dependence of the total compensation on a variety of factors relating to the type and magnitudes of the economic losses, medical and wage loss, and to the type and severity of injury has been explored by prior researchers who found medical losses to be the primary determinant of total compensation but they also found that other severity variables play a distinct and significant role in the final settlement values. Further research introduced the notion that both the information gathered in the course of investigation and the adjuster’s attitude toward the quality of the claim, especially the suspicion of fraud, also played a significant role in the final settlement value. Recently, it has been shown that settlement values for subjective injury claims are systematically lower relative to special damages and indicate that insurers use their negotiating power to obtain lower settlements on questionable claims as a rational response to the presence of fraud and build up claims. The current paper extends that research by examining additional variables specifically related to the investigation and negotiation processes and quantifying the effect of those variables on the final total compensation. In particular, we find that strain and sprain claims command lower general damages relative to specials, even in the absence of suspicion of fraud and build up, but that the intensity of suspicion of fraud and build up can reduce overall payments as much as 24 percent. For the first time, the negotiating effect of attorney demands enters the quantitative model in addition to the usual contingency fee. Finally, evidence that insurers are isolating low impact collisions and reducing the compensation through negotiation is explored and quantified.